Pengaruh E-Service Quality Dan Promosi Terhadap Kepuasan Pelanggan Grabfood Pada Generasi Z Di Bali - G A Ayu Putu Pritta Devi Pradnyan Andari; Fitriani Nur Utami (Universitas Telkom, 2024)
Online food delivery (OFD) has now become an important requirement for the people of Indonesia, so that OFD servicesare now competing to provide the best satisfaction to their customers. In Indonesia, OFD services vary. Grab with theOFD function, namely Grabfood. With many competitors, Grabfood must always provide maximum service and attractiveincentives for customers to be satisfied with the services provided. The purpose of this study is to identify and analyze theimpact of advertising and e-service quality on customer satisfaction, either partially or simultaneously, among GenerationZ in Bali. The method used in this research is a quantitative method combined with a descriptive method. The scale usedis the Likert scale and several linear regression tests, partial tests ( t test) and simultaneous tests (F test) are used toanalyze the data. Electronic service quality, promotion and customer satisfaction are at the appropriate level, proportional toeach variable. Then, the results of the promotion test show that partially and simultaneously, the quality of e-serviceshas a significant influence on GrabFood customer satisfaction in Generation z Bali. The influence of the independentvariables quality and promotion of electronic services on the dependent variable, namely customer satisfaction, is 69.2%.The remaining 30.8% is an influence variable that was not examined carefully in this research.